Temperatures and substrates for germination and vigor of Erythroxylum pauferrense Plowman seeds (Acta Scientiarum. Biological Sciences, 2019)
Erythroxylum pauferrense is an endemic understory plant species of the Northeast Region of Brazil. The species is of great importance to the region and so ecophysiological studies are needed for its preservation. The objective of the present study was to determine the best substrates and temperatures for testing germination and seed vigor of E. pauferrense. An experiment was performed comprising a completely randomized design in a 5 x 4 factorial scheme, with five temperature regimes (20, 25, 30, 35°C constant and 20-30°C alternating) and four types of substrates (paper, vermiculite, sand and commercial substrate). The following characteristics were evaluated: germination percentage, first germination count, germination speed index, mean germination time, seedling length and dry mass (root and shoot). Paper and vermiculite substrates combined with constant temperatures of 20, 25, 30 and alternated between 20-30°C, provide greater seed germination and vigor while 35°C reduces seed physiological quality.